Influence of Principal Leadership, Work Motivation, and Job Satisfaction on Teachers' Performance - Andriani Sariwardani; Ifat Yuliawati; Ipah Afifah; Mita Rianti (Journal Management & Economics Review (JUMPER), 2026)
This study aims to analyze the influence of principal leadership, work motivation, and job satisfaction on teachers’ performance. A quantitative approach with an explanatory research design was employed to examine both partial and simultaneous relationships among the variables. Data were collected through structured questionnaires distributed to 150 teachers using proportionate stratified random sampling. The data were analyzed using multiple linear regression analysis. The results indicate that principal leadership has a positive and significant effect on teachers’ performance. Work motivation was found to be the most dominant factor influencing performance, demonstrating that teachers with higher levels of intrinsic and extrinsic motivation tend to exhibit better instructional effectiveness and professional responsibility. Job satisfaction also significantly affects teachers’ performance, suggesting that teachers who experience favorable work conditions and organizational support are more likely to perform optimally. Simultaneously, principal leadership, work motivation, and job satisfaction significantly influence teachers’ performance, explaining 50.7% of the variance. These findings highlight the importance of strengthening school leadership practices, enhancing teacher motivation, and improving job satisfaction to achieve sustainable improvements in educational performance. The study provides practical implications for school administrators and policymakers in developing integrated strategies to enhance teacher effectiveness.